2006
DOI: 10.2514/1.16658
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Transonic Buffet on a Supercritical Airfoil

Abstract: The steady/unsteady flow of the BGK No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 24 publications
6
22
0
Order By: Relevance
“…Shock movement in such a configuration is known as "the buffeting phenomenon". Recent numerical investigations (Deck, 2005;Xiao and Tsai, 2006) support the theory proposed by Lee (1990) who suggested that the separation (point 2 in figure 6) causes large scale structures that are convected downstream. As these structures reach the trailing edge (point 1 in figure 6) they interact with the flow coming from underneath the airfoil.…”
Section: Comparison With Other Studiessupporting
confidence: 59%
“…Shock movement in such a configuration is known as "the buffeting phenomenon". Recent numerical investigations (Deck, 2005;Xiao and Tsai, 2006) support the theory proposed by Lee (1990) who suggested that the separation (point 2 in figure 6) causes large scale structures that are convected downstream. As these structures reach the trailing edge (point 1 in figure 6) they interact with the flow coming from underneath the airfoil.…”
Section: Comparison With Other Studiessupporting
confidence: 59%
“…The positive time delays are obtained, indicating that the pressure disturbances within the separated region behind the shock wave propagate downstream towards the aerofoil trailing edge. The local propagation speed of the pressure disturbances can be calculated by dividing the spatial distances between the neighbouring probes by the time delays between the peaks of the corresponding cross-correlations (Xiao et al 2006). Then, the speed is determined as approximately 0.34U ∞ , consistent with the convection speed of the coherent vortical structures, 0.35U ∞ , given above.…”
Section: Pressure Power Spectral Analysis In Turbulent Boundary Layermentioning
confidence: 89%
“…Lee 1990; Xiao, Tsai & Liu 2006), we notice that there exist two typical differences between the present type C and the type A shock wave motion. As a symmetrical aerofoil is considered, unlike only an oscillating shock wave on the upper surface of a supercritical aerofoil (Lee 1990;Xiao et al 2006), the upstreampropagating shock waves occur alternately between the upper and lower surfaces. The period of shock wave motion in this problem is referred to as the complete process of both the shock waves propagating upstream and leaving the aerofoil, as shown in figure 7.…”
Section: Feedback Model Of Shock Wave Motionmentioning
confidence: 99%
“…From large eddy simulations to dedicated turbulence models connected to the unsteady Reynolds averaged method [4], [5], [6] there is no generally robust method especially in three dimensions, even if large meshes are to be employed, from 0.2 to 1 billion cells, making the computation expensive, time consuming and requiring experts in the field, which need years of dedicated, sustained work on this specific topic, for which funding is not persistent. It is difficult or impossible in a normal project timeframe to try to align the experimental results with the numerical work, since the current wind tunnel model has laminar areas combined with turbulent contaminated areas due to steps and gaps, as the current model is built, which nearly makes impractical the use of regular CFD methodology.…”
Section: Incas Bulletin Volume 7 Issue 2/ 2015mentioning
confidence: 99%